Avaliação da capacidade de centralização e transporte do canal após preparo com os sistemas Pro Taper Next e Twisted File Adaptive - Pacheco, Paulo de Tarso Gondim (2016)
The present study evaluated the canal transportation and the centering ability of ProTaper Next (PTN) and Twisted File Adaptive (TFA) systems using micro- computed tomographic (micro-CT) imaging. Twenty isthmus-containing mesial roots of mandibular molars were anatomically matched based on similar morphological dimensions using micro-CT evaluation (resolution of 14.25 μm) and assigned to 2 experimental groups (n = 10) according to the system used for root canal preparation: PTN and TFA groups. Then, the specimens were scanned again and the matched images of the mesial canals, before and after preparation, were examined at 3 cross-section levels (3-mm, 5-mm and 7-mm from the apical end of the root) to analyze the canal transportation and the centering ratio. Independent samples t-test was used to compare the canal transportation and centering ratio between the groups. All statistical procedures were performed with a significance level set at 5%. Root canals prepared with either PTN or TFA systems were found to present similar canal transportation and centering ratio at all levels (p > 0.05). Both systems presented similar results regarding canal transportation and centering ability.